Design and development of an automatic liquid fertilizer dosing device - Sum, Wen Wei. (2010)
Aquarium hobbyists have always wanted to have a healthy aquarium with beautiful flourishing aquatic plants in it. One of the major factors is to provide precise liquid fertilizer dosage for the plants and therefore, an automatic liquid fertilizer dosing mechanism is required. However, currently in the market, there is no mechanism that can carry out this task appropriately.